PENGGUNAAN PROYEKSI TREN DI UMKM NN UNTUK MEMENUHI PERMINTAAN KONSUMEN - Nur Safina; Erna Indriastiningsih; Agung Widiyanto Fajar Sutrisno (POLITEKNIK LP3I JAKARTA, 2024)
MSMEs (Micro, Small and Medium Enterprises) in Indonesia have a major influence in terms of economic growth. NN MSMEs are MSMEs engaged in culinary. One type of NN MSME product is ready-to-eat emping. Often during the Eid al-Fitr holiday experience overwhelmed in terms of meeting the demand for ready-to-eat emping. This study aims to assist NN MSMEs in estimating the amount of consumer demand for ready-to-eat emping, as well as to find out the best results and methods in calculating forecasting in trend projection methods. The trend projection method used in forecasting calculations in this case is linear regression and least squares. Meanwhile, to calculate the error value from the forecasting results using the Mean Absolute Deviation (MAD), Mean Squared Error (MSE), Mean Absolute Percentage Error (MAPE) methods. The best method from the results of this study is to use a linear regression method with demand values for 2024, 2025 and 2026 during Eid al-Fitr are 1771.23 kg, 1914.24 kg, and 2057.25 kg respectively with error values of MAD, MSE and MAPE respectively are 612.0781, 525807.4 and 48.83%. Keywords: Forecasting, Trend Projections, MSMEs, Consumer Demand